Well-being Messaging for Mammalian Milks: A Scoping Review - Moradi, Saleh; Hort, Joanne (Frontiers in Nutrition, 2021)
Having a holistic understanding of research regarding well-being messaging for milk is vital to allow the optimal communication of the association between milk consumption and various nutritional, physical and psychological benefits to the consumer. This work is a unique interdisciplinary, scoping review of existing research on well-being messaging for milk. Well-being messages are ways to communicate the broad well-being benefits of specific products to the consumer through information on food content or statements that link the product with favourable components, functions or well-being outcomes. Leveraging this broad definition, and by proposing a guiding theoretical model that considers well-being messaging as a form of communication, milk well-being messaging literature has been mapped across time, geographical locations, disciplines, and product types. 246 were records included in this review, of which 177 were empirical studies. Studies were disseminated between 1954 and 2019, with 54.9% published after 2011. Food, Agriculture, and Biological Sciences (N = 109), Nutrition and Dietetics (N = 78), Medicine, Public Health, and Health Professions (N = 69) disciplines have attracted the most publications, with numbers generally increasing in most recent years. The majority of included non-empirical records (69.6%) provide lists of commercially available products carrying well-being messaging and/or regulations regarding the use of particular well-being messages for milk according to various legislative authorities. Most of the empirical studies were conducted in North America (N = 71), West Europe (N = 52), and Oceania (N = 22), and on plain (i.e., unflavoured) milk (N = 152). Whereas most studied elements of well-being messaging for milk across time, i.e., message (N = 169), product (N = 141), receiver (N = 101), and context (N = 72), have seen an increasing number of studies in recent years, sender (N = 51) and medium (N = 27) have been even less studied in the past four years. A more detailed analysis of research trends in each element of well-being messaging is reported. The research highlights immediate and strategic knowledge gaps that need further attention from researchers and/or policy makers in order to improve the ‘messaging’ of milk consumption’s well-being benefits to the consumer.